Diversas presentaciones clínicas de los aneurismas de la arteria esplénica: Cuatro nuevas observaciones nacionales - Montano, Daniel; Harretche, Martín; Berhouet, Horacio; Rodríguez, Gustavo; Segura, Daisy; Fenocchi, Eduardo (Cirugía del Uruguay, 1994)
The authors add 4 new cases of aneurysms of the splenic artery to national literature. Diangosis was intra-operative in al! cases. In one of them a retrogastric tumor had been seen endoscopically; in two male patients who had been operated on urgently with diagnosis of haemoperitoneum, this pathology had been suspected; and the other case was a finding in the course of gastrectomy.